HUBUNGAN DUKUNGAN SUAMI DAN STATUS GIZI DENGAN KEJADIAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI PUSKESMAS RUSIP ANTARA KAB. ACEH TENGAH - Bakara, Sri Muliana Putri; Paradila; Jamilah (LPPM Universitas Sari Mulia, 2022)
Background:Nausea and vomiting usually occur only in the first trimester, but 20% of women experience these symptoms throughout pregnancy. Hyperemesis gravidarum is found in only 1–20 cases per 1,000 pregnant women. Although this condition is relatively rare, it has significant clinical and social impacts. Husband’s support is important during pregnancy because the husband is the closest person to the expectant mother. He is expected to continuously motivate and accompany her. Moreover, the support provided by the husband during pregnancy can help reduce anxiety and restore the mother’s confidence in going through the pregnancy process. Objective:To determine the relationship between husband’s support and nutritional status with the incidence of hyperemesis gravidarum among first trimester pregnant women at the Rusip Antara Community Health Center, Central Aceh District. Method:This study used an analytical survey method with a cross-sectional design. Data were collected at one point in time using accidental sampling. The sample consisted of 46 first-trimester pregnant women. Results:The study found a relationship between husband’s support and nutritional status with the incidence of hyperemesis gravidarum among pregnant women in the first and second trimesters. Pregnant women with poor nutritional status were found to have a 10.3 times higher risk of experiencing hyperemesis gravidarum compared to those with good nutritional status. Conclusion:There is a relationship between husband’s support and nutritional status with the incidence of hyperemesis gravidarum among first trimester pregnant women. Keywords: Hyperemesis gravidarum, husband’s support, nutritional status